2020
DOI: 10.1177/1550059420922744
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal, Prospective Study to Evaluate the Effects of Treatment on the Inhibitory Control Function After Transsphenoidal Surgery for Pituitary Adenomas

Abstract: Objectives: Injured cognitive abilities have been reported in patients with pituitary adenoma. However, to date, few researchers have directly investigated the electrophysiological study of inhibitory control function of pituitary patients both pre- and postsurgery. Thus, this study aimed to identify the factors affecting the inhibitory control function of pituitary patients. Methods: Thirty presurgery pituitary patients were recruited and 26 patients of them completed the postsurgery follow-up. Thirty healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The written informed consent was fully understood and signed by all participants. The inclusion and exclusion criteria were described in our previous work ( 32 ). Patients were included if (1) a prolactin-secreting pituitary tumor was discovered ( 33 , 34 ), (2) they had never undergone a craniotomy or received radiation therapy, (3) they were able to fulfill ERP examinations, and (4) their age ranged from 20 to 50 years old, with all of them completing at least secondary school education.…”
Section: Methodsmentioning
confidence: 99%
“…The written informed consent was fully understood and signed by all participants. The inclusion and exclusion criteria were described in our previous work ( 32 ). Patients were included if (1) a prolactin-secreting pituitary tumor was discovered ( 33 , 34 ), (2) they had never undergone a craniotomy or received radiation therapy, (3) they were able to fulfill ERP examinations, and (4) their age ranged from 20 to 50 years old, with all of them completing at least secondary school education.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to functional imaging, decreased working and verbal memory scores are associated with altered perfusion in the temporal areas [71]. Furthermore, electroencephalographic studies have suggested alterations in conflict monitoring [83].…”
Section: Supratentorial Tumorsmentioning
confidence: 99%